Green Biosynthesized Silver Nanoparticles With Aqueous Extracts of Ginkgo Biloba Induce Apoptosis via Mitochondrial Pathway in Cervical Cancer Cells - Xu, Zhen; Feng, Qi; Wang, Min; Zhao, Huange; Lin, Yingying; Zhou, Songlin (Frontiers in Oncology, 2020)
Biosynthetic silver nanoparticles (AgNPs), specifically formed using medicinal plant extracts, have recently exhibited a remarkable therapeutic effect due to their anticancer potential. Here, we synthesized AgNPs using an aqueous extract of Ginkgo biloba leaves and evaluated its activity against cervical cancer (CCa) and the related molecular mechanisms. The physiochemical properties of the AgNPs were measured by ultraviolet-visible spectrophotometry, nanometre particle size analyzer and transmission electron microscopy. The AgNPs effects on cell proliferation and apoptosis were investigated through MTT, MTS, and colony formation assay; Hoechst 33258 staining; and flow cytometry. The intracellular ROS and oxidative stress levels were assessed using the appropriate commercial kits. Apoptosis-related protein levels were determined by western blotting. We prepared a series of different sized ginkgo extract-synthesized AgNPs (GB-AgNPs), and the smallest mean particle size was 40.2±1.2 nm with low polydispersity (0.091±0.011), zeta potential values showed -34.56 mV. Compared to the controls, the GB-AgNP treatment inhibited the cell proliferation and induced the apoptosis of HeLa and SiHa cells. In addition, GB-AgNP treatment led to markedly increased levels of intracellular ROS, the release of cytochrome c (Cyt C) from mitochondria into the cytosol and the cleavage of caspase -9 and -3 in both CCa cell lines. Moreover, NAC, an ROS scavenger, eliminated the effect of GB-AgNPs on the HeLa and SiHa cells. This study reveals that GB-AgNPs suppresses cancer cell proliferation and induces apoptosis by upregulating intracellular ROS generation and inducing the activation of the caspase-dependent mitochondrial apoptotic pathway in CCa cells. Thus, GB-AgNPs may be a potential alternative drug for CCa therapy.